The Impact of Self-correction on the Descriptive Text Writing Achievement of Grade VIII Students in Madrasah Tsanawiyah Aulia Cendekia Palembang - Shella Mitha Barida; Jaya Nur Iman; Nike Angraini; Desi Surayatika (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study investigates the effect of the self-correction technique on improving descriptive text writing skills among Grade VIII students at Madrasah Tsanawiyah Aulia Cendekia Palembang. A pre-experimental design with a one-group pre-test and post-test was used, involving 42 students. Results showed a significant improvement in students' writing scores, from a pre-test mean of 38.52 to a post-test mean of 64.98. Statistical analysis with a paired- sample t-test (t = -25.563, p < 0.001) confirmed a positive effect. The findings suggest that self- correction enhances students’ awareness of mistakes, promotes learning independence, and improves writing skills.